FACTORS INFLUENCING CONSUMER BEHAVIOR IN PREFERENCE FOR DOUYIN (TIKTOK) IN CHINA - Chen, Jiayi; Syriac, Nellikunnel (INTI International University, 2023)
The high rate of Internet use per capita in China has contributed to the meteoric rise in the number of people using Douyin. The purpose of this study is to investigate the factors that contribute to the preference for Douyin held by Chinese consumer behaviour among Chinese in China. The models developed by Brackett and Carr (2001) serve as the primary basis for this investigation's theoretical framework. Concerning factors include service quality, technological advancements, marketing strategies, and advertising campaigns. Using the reseach method of convenience sampling, a total of 450 samples were obtained from Internet users in China. The findings of this investigation indicated that all three factors contributed to China's fondness for Douyin as a literary form. According to the findings of the study, marketing and advertising are the variables that have the most impact on people's decisions to use Douyin; hence, the company implication might invest more money in these endeavours. This study demonstrated that the research gap may be analysed from the point of view of the underlying theory, which is the study's addition to the theoretical body of knowledge. At the very conclusion of the study, more restrictions as well as proposals for the future are discussed.